Peran Pembelajaran Bahasa Arab Kontekstual dalam Penguatan Profil Pelajar Pancasila - Mu’alim Wijaya; Muhammad Danial Shiddiq; Miharul Faiq (Lembaga Yasin AlSys, 2025)
Contextual Arabic language instruction at MA Nurul Jadid is positioned as a key strategy for cultivating student character aligned with Pancasila values, particularly in response to the prevailing tendency of Arabic language teaching to focus narrowly on formal linguistic aspects that are less meaningful for everyday life. This study aimed to describe the role of contextual Arabic language learning in strengthening the Profil Pelajar Pancasila (Pancasila Student Profile, PPP) at MA Nurul Jadid. Employing a qualitative approach with a case study method, data were collected through classroom observations, interviews, and documentation of teaching practices. The findings show that the contextual approach contributes positively to strengthening all six PPP dimensions, with particular emphasis on the gotong royong dimension through group work and the critical reasoning dimension through the analysis of religious texts. The implementation of learning activities such as discussions, conversation simulations, and the systematic linking of lesson content to students’ daily lives makes Arabic language learning more engaging, relevant, and meaningful. In conclusion, context-based Arabic language instruction has the potential to serve as an effective strategy for supporting the implementation of Kurikulum Merdeka in shaping learners with a Pancasila-oriented character. The practical implications of this study underscore the importance of professional development for Arabic language teachers in designing contextual learning that is systematically integrated with PPP values so that character formation can proceed in a more structured and sustainable manner.